The Motivational Trifecta: Empirical Study Of Industrial Culture, Internships, And Learning Community In Vocational Teacher Engagement - Waryanto Waryanto; Maryanto Maryanto; Ngasbun Egar (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2025)
Teachers’ work motivation is a critical factor directly impacting their performance, job satisfaction, and a school's overall success. Furthermore, the integration of Seiri industrial culture, which emphasizes organization and efficiency, with teacher internship programs is a key strategy for vocational schools to prepare graduates with the practical competencies and professional work ethic needed by modern industries. This research was designed to analyze the influence of industrial culture, productive teacher internship programs, and learning communities on the work motivation of vocational high school (Sekolah Menengah Kejuruan, SMK) teachers across Kendal Regency, both partially and simultaneously. Employing a quantitative approach with an explanatory research design, the study encompassed all public and private vocational high schools in Kendal Regency, Central Java Province, totaling 29 institutions. The population of this research comprised 315 productive teachers. A sample of 176 teachers was determined through the application of the Slovin formula. Proportional sampling was the technique utilized for sample selection. Data collection was conducted via questionnaires. The data were analyzed using multiple linear regression analysis techniques. The findings of this research indicate that industrial culture, productive teacher internship programs, and learning communities exert a positive and significant influence on the work motivation of vocational high school teachers in Kendal Regency, both partially and simultaneously. This research significantly contributes to the fields of educational psychology and human resource management by providing a robust theoretical framework and empirical evidence on the factors influencing teacher work motivation in vocational education.